Essential oil-loaded antimicrobial and antioxidant zein/poly(lactic acid) film as active food packaging. (December 2022) - Ge, Xiaohan; Huang, Xueying; Zhou, Liping; Wang, Yi
Abstract: Food spoilage and poisoning can be caused by microbes in food. Active food packaging with the addition of antimicrobial compounds is a novel method to prolong the shelf life of food and improve product quality. PLA, a very popular synthetic biodegradable material, was mixed with zein, a widely studied food packaging material, and the plasticizer PEG to make a composite film ZLP. With the addition of PLA, the brittleness of zein film was reduced and the water barrier properties of zein and PEG composite film was enhanced. The mass ratio of zein, PLA, and PEG for the optimal mechanical and water barrier properties of the film was 5:5:2. High antioxidant effects were obtained in the eugenol- and carvacrol-loaded ZLP films, while good antibacterial effects against E. coli and S. aureus were found in the carvacrol- and cinnamaldehyde- loaded ZLP films. Highlights: Zein and poly(lactic acid) (PLA) were blended to make active biodegradable packaging. Polyethylene glycol was used as plasticizer and compatibilizer. Mechanical and water barrier properties of zein films were largely improved. Four kinds of essential oil were added as antimicrobial agent and antioxidant. Essential oil loaded film showed excellent antibacterial and antioxidant properties.